Unpaved Road Reinforced with Geosynthetics. (2016) - Calvarano, Lidia Sarah; Palamara, Rocco; Leonardi, Giovanni; Moraci, Nicola
Abstract: Geosynthetics are commonly used in mechanically stabilization of unpaved roads with a low volume of traffic. The practical use of geosynthetics above a weak subgrade or within a base course has demonstrated the benefit of reducing rut depths and prolonging pavement life. The purpose of this paper is to provide design criteria currently available for reinforced unpaved roads. This paper deals with the results of a parametric analysis varying soil and geosynthetic mechanical properties, allowable depth rut and traffic conditions. The focus of the present study is to compare these different design procedures aimed at estimating the base thickness required for reinforced unpaved roads, providing their improvements and limits. Design procedures are also compared with data obtained from field tests.